KEDUDUKAN SUAMI-ISTRI (KAJIAN SURAH AN-NISA’ [4]: 34) - Rahmawati Hunawa (Potret Pemikiran, 2018)
Abstract. This paper examined the position of husband and wife in according to Islam. Qs. an-Nisa '[4]: 34 becomes the focus of the reference and analysis on this topic. Qs Study. an-Nisa [4]: 34 highlights a lot about women. This Surah became the liberator of women from the injustice of society towards women since 15 centuries ago. In marriage, husbands are obliged to lead and protect their wives and all family needs, while women on the male side are like body organs on a body, men as heads, and women as bodies. Qs. an-Nisa '[4]: 34 explains the position of men is higher than women, this is intended to reinforce the division of tasks between men as husbands and women as wives. The mention of the words ar-Rijal and an-Nisa  in this verse does not emphasize biological significance, but rather character leadership and social functions. The figure of leadership (qawwam) is generally more dominantly indicated by men than women. The virtue of men in this verse is related to his responsibilities as head of the household. However, al-fadhl (excess) possessed by men does not make men (husbands) doing arbitrarily on their women (wives).  Keywords : Al-Rijal, An-Nisa‟, Qawwamun  Abstrak. Paper ini mengkaji tentang kedudukan suami dan istri dalam Islam. Qs. anNisa’ [4]: 34 menjadi fokus acuan dan analisis tentang topik ini. Kajian Qs. an-Nisa [4]: 34 ini banyak menyoroti tentang perempuan. Surah ini menjadi pembebas perempuan dari ketidakadilan masyarakat terhadap perempuan sejak 15 abad silam. Dalam pernikahan, suami wajib memimpin dan melindungi  isteri serta segala keperluan keluarga, sedangkan wanita di sisi kaum pria adalah laksana organ tubuh dalam raga yang satu, kaum pria sebagai kepala, sedangkan wanita sebagai badannya. Qs. an-Nisa’ [4]: 34 menjelaskan kedudukan laki-laki  lebih tinggi  dari perempuan, hal ini dimaksudkan untuk mempertegas pembagian tugas antara lakilaki sebagai suami dan perempuan selaku isteri. Penyebutan kata ar-Rijal dan anNisa’ dalam ayat ini tidak menekankan pada signifikansi biologis, tetapi lebih kepada kepemimpinan karakter dan fungsi sosial. Sosok kepemimpinan (qawwam) umumnya lebih dominan ditunjukkan oleh kaum laki-laki daripada perempuan. Keutamaan laki-laki dalam ayat ini dihubungkan dengan tanggung jawab nya sebagai kepala rumah tangga. Namun, al-fadhl (kelebihan) yang dimiliki oleh lakilaki lantas tidak menjadikan laki-laki (suami) berbuat semena-mena terhadap perempuan (isteri) nya.  Kata Kunci : Al-Rijal, An-Nisa‟, Qawwamun